LOSS OF SMELL AND TASTE IN COVID19 PATIENTS - Dr. Asaad Saber Faraj; Dr. Mohammed Abdul Wahhab Mohammed (Scholar Express Journals, 2022)
This study focuses on the assessment and knowledge of loss of smell and taste in covid19 patients. As 200 patients were collected from Azady Teaching Hospital, Kirkuk, Iraq . The samples were divided into 67 women and 124 men, The average age of patients ranged from 30 to 66 years as they were diagnosed with COVID-19 infection by rt-PCR for respiratory samples and through the use of a questionnaire consisting of a number of questions in assessing symptoms of olfactory loss and age and it was found that there is a significant linear relationship of 0.001, and this indicates that there is a large role for co-19 on the prevalence of loss of sense of smell and taste.
Keywords: COVID-19; smell; taste; Anosmi